The Study of Time-Space Dynamics of Knowledge with Innovation Biographies - Anna Butzin; Brigitta Widmaier (Philipps-University Marburg, Department of Geography, 2012)
The paper presents the methodology of Innovation Biographies that has been designed to study the time-space dynamics of knowledge and ways of knowledge combination in innovation processes. Innovation Biographies allow capturing relationships, contextual settings and different kinds of knowledge and enable insights into the evolvement and development of innovations. By following the process of creation with specific interviewing methods and triangulation, the biography of an innovation is reconstructed including the evolution of related knowledge. Data collection is able to transcend sectoral as well as local, regional or national categories and sheds light on cross-sectoral knowledge combinations and its multi-scalar reach.
Keywords: D83; O12; O31; R11; 330; Innovation Biographies; knowledge dynamics; knowledge combinations; time-space paths; multi-level view